IMPLEMENTASI PERATURAN DAERAH NOMOR 02 TAHUN 2022 PASAL 14 AYAT 1 TENTANG PERLINDUNGAN DAN PEMBERDAYAAN PETANI - Usrotul Hasanah; Hasan Muchtar Fauzi (Universitas Bina Taruna Gorontalo, 2024)
The aim of this research is to analyze the implementation of Regional Regulation Number 02 of 2022 Article 14 Paragraph 1 concerning the protection and empowerment of farmers. The type of research used in this research is Field Research. Providing BK 01 and BK 02 Situbondo Agritan Rice Seeds in Mimbaan Village, Panji District, Situbondo Regency regarding the Protection and Empowerment of Farmers. BK Situbondo 01 and BK-02 are new superior variety seeds (VUB) which are capable of producing rice in larger quantities with a shorter planting period, problems arise, for example farmers' doubts about the quality of the seeds, unknown technology to increase production, handling pests arising from new seeds, adaptation to unpredictable weather and lack of land for making natural fertilizer to ferment, and the research results are going well. and the conclusion is that the seeds provided are good, according to the seeds that farmers want, which are resistant to pests, short planting periods and high grain yields. The government also provides assistance until harvest, apart from providing technology for making organic fertilizer and making its own pesticides.